Oceanographic barriers, divergence, and admixture: Phylogeography and taxonomy of two putative subspecies of short‐finned pilot whale. Issue 11 (2nd June 2019) - Van Cise, Amy M.; Baird, Robin W.; Baker, Charles Scott; Cerchio, Salvatore; Claridge, Diane; Fielding, Russell; Hancock‐Hanser, Brittany; Marrero, Jacobo; Martien, Karen K.; Mignucci‐Giannoni, Antonio A.; Oleson, Erin M.; Oremus, Marc; et al.
Abstract: Genomic phylogeography plays an important role in describing evolutionary processes and their geographic, ecological, or cultural drivers. These drivers are often poorly understood in marine environments, which have fewer obvious barriers to mixing than terrestrial environments. Taxonomic uncertainty of some taxa (e.g., cetaceans), due to the difficulty in obtaining morphological data, can hamper our understanding of these processes. One such taxon, the short‐finned pilot whale, is recognized as a single global species but includes at least two distinct morphological forms described from stranding and drive hunting in Japan, the "Naisa" and "Shiho" forms. Using samples ( n = 735) collected throughout their global range, we examine phylogeographic patterns of divergence by comparing mitogenomes and nuclear SNP loci. Our results suggest three types within the species: an Atlantic Ocean type, a western/central Pacific and Indian Ocean (Naisa) type, and an eastern Pacific Ocean and northern Japan (Shiho) type. mtDNA control region differentiation indicates these three types form two subspecies, separated by the East Pacific Barrier: Shiho short‐finned pilot whale, in the eastern Pacific Ocean and northern Japan, and Naisa short‐finned pilot whale, throughout the remainder of the species' distribution. Our data further indicate two diverging populations within the Naisa subspecies, in the Atlantic Ocean and western/central Pacific and Indian Oceans, separated by the Benguela Barrier off South Africa. This study reveals a process of divergence and speciation within a globally‐distributed, mobile marine predator, and indicates the importance of the East Pacific Barrier to this evolutionary process.